2004
DOI: 10.1093/jxb/erh050
|View full text |Cite
|
Sign up to set email alerts
|

Catalase activity and expression in developing sunflower seeds as related to drying

Abstract: Changes in catalase (CAT) activity and in CAT isoform pattern and expression were investigated in developing sunflower (Helianthus annuus L.) seeds during desiccation on the mother plant and after artificial drying on the flowerheads. Seeds regularly desiccated during their development on the mother plant and reached mass maturity at c. 42 d after flowering (DAF). Freshly harvested seeds did not germinate at any stage of development because they were dormant, but their dormancy was broken after 5-6 months of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
69
1
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(81 citation statements)
references
References 37 publications
8
69
1
3
Order By: Relevance
“…Our results clearly showed that increased SOD activity appears to effectively mop up oxygen radicals during the early stage of maturation. Similarly, an increased SOD activity has been observed during seed maturation (Bailly et al, 2004). Analysis with native PAGE suggested there are five SOD isoforms visualized during seed maturation, but different isoform patterns were observed.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Our results clearly showed that increased SOD activity appears to effectively mop up oxygen radicals during the early stage of maturation. Similarly, an increased SOD activity has been observed during seed maturation (Bailly et al, 2004). Analysis with native PAGE suggested there are five SOD isoforms visualized during seed maturation, but different isoform patterns were observed.…”
Section: Resultsmentioning
confidence: 79%
“…The CAT activity has been shown to increase during seed development and is dependent on seed moisture content in sunflower (Bailly et al, 2004). However, no changes in the CAT activity were found during seed maturation, and the activity remained low, representing only 16 U/g fresh weight.…”
Section: Resultsmentioning
confidence: 97%
“…Catalase and peroxidase converts hydrogen peroxide into compounds that are non-toxic to cells. The efficiency of the enzymatic, detoxification activity of the reactive species, especially of catalase, increases during seed development and is closely linked to the moisture content in sunflower seeds (BAILLY et al, 2004). In contrast, the activities of peroxidase and glutathione reductase decreased during desiccation of Triticum durum seeds (DE GARA et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…In addition many environmental factors such as light (Feierabend et al, 1992) temperature (Omran, 1980;Nir et al, 1986), O 2 and CO 2 concentration (Fair et al, 1973;Monk et al, 1987) have been shown to influence catalase activity in mature plants. In fact this high level of CAT activity induced by grains drying was associated with a decrease in hydrogen peroxide level and in lipid peroxidation studied by Bailly et al (2004).…”
Section: Discussionmentioning
confidence: 87%
“…In our study highest activity of CAT was observed in grains which are in agreement with previous finding on Nigella sativa in which Kaleem et al (2006) observed high activity in grains. An increased CAT activity in sunflower (Helianthus annuus) grains was associated with a decrease in hydrogen peroxide level and in lipid peroxidation (Bailly et al, 2004). Activity of CAT is altered due to metabolic changes during various growth stages.…”
Section: Discussionmentioning
confidence: 99%